1991
DOI: 10.1002/jor.1100090616
|View full text |Cite
|
Sign up to set email alerts
|

Response of cortical bone to local controlled release of sodium fluoride: The effect of implant insertion site

Abstract: In a previous experiment, sodium fluoride in a biodegradable polymer matrix was introduced into the femoral canal of the rabbit and bone formation was compared with contralateral controls. We noted significant bone formation, but only in the distal third of the periosteal surface of the femur. This experiment was performed to distinguish fluoride-induced periosteal bone formation from that due to the reactive osteogenic changes associated with local injury caused by the process of implantation. A proximal appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The incorporation of trace essential elements into biomaterials has proven to be an effective way to stimulate bone formation. [3][4][5] Studies in vitro and in vivo have demonstrated that zinc (Zn) is able to stimulate bone formation and to inhibit bone resorption. [6][7][8] However, Zn must be released slowly from the implant surface because Zn at elevated levels induces adverse reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of trace essential elements into biomaterials has proven to be an effective way to stimulate bone formation. [3][4][5] Studies in vitro and in vivo have demonstrated that zinc (Zn) is able to stimulate bone formation and to inhibit bone resorption. [6][7][8] However, Zn must be released slowly from the implant surface because Zn at elevated levels induces adverse reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification aims to accelerate osseointegration and includes hydroxyapatite (HA) coatings, mechanical blasting (using either Al 2 O 3 or TiO 2 particles), anodic oxidation and acid-etching processes (different concentrations of H 2 SO 4 , HF, HNO 3 and HCl). Recently, some authors have reported on significantly improved bone tissue reactions by modification of surface oxide properties of titanium implants 1,19 or ion release 2 . Chemical modification of titanium implant surface is of particular interest because it may enhance osseointegration without embedding surface contaminants, such as grit particles 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Results reported from in vitro experiments indicate that fluoride ions influence formation of both organic and inorganic components of bone tissue. Thus, fluoride may increase the density of trabecular bone and enhance the incorporation of collagen into bone matrix as well as alkaline phosphatase activity (Shteyer et al 1977;Farley et al 1983;Andersson et al 1993).…”
mentioning
confidence: 99%